Pengaruh Negative Framing dan Monitoring Control terhadap Eskalasi Komitmen dalam Pengambilan Keputusan Investasi - Ulya Puspita Sari; Sany Dwita (Universitas Negeri Padang, 2024)
This study aims to examine the effect of Negative framing and Monitoring Control on escalation of commitment in investment decision making. This study uses a 2x2 factorial design with four treatments. The hypothesis in this study was tested using the One Way ANOVA test. This study used Accounting SI students at UNP. Using 4 scenario cases, participants were asked to make decisions to see how negative framing and monitoring control affect escalation of commitment when managers will make decisions. The results of this study indicate that negative framing affects managers when making decisions, this is due to the information received by managers. While monitoring control shows the same thing, monitoring control makes managers not escalate their decisions because of supervision.